Memberdayakan Pelaku Usaha Jamur Sawit Krispi Melalui Pelatihan Pengurusan Izin P-IRT dan Pembukuan Digital - Henny Indrawati; Caska Caska; Vonny Setiaries; Gimin Gimin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Crispy oil palm mushroom is made of oil palm mushroom and has been produced by producers for approximately ten years. Unfortunately, this home-based business of mushrooms has not yet secured a permit from authorities, and the producers have not regularly recorded the sales. Therefore, this community program aims to empower the producers of crispy oil palm mushrooms by providing training and mentoring on the process of obtaining a home-based industry of food production permit and digital bookkeeping. The program's success was measured by the results of the assessment in a questionnaire, by identifying the participants' motivation to process the permit and by implementing digital bookkeeping. The program successfully enhanced the producers’ knowledge and understanding of the home-based industry of food production permits and digital bookkeeping. The producers have obtained the business permit number 2041405010034-27, and they have also implemented digital bookkeeping to record sales.